Pengaruh Pengawasan Dan Sanksi Terhadap Disiplin Kerja Dengan Motivasi Sebagai Variabel Intervening (CV. Mubarokfood Cipta Delicia Kudus) - Umdhatun Niswah; Eko Nur Fu’ad (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
This research aims to analyze the influence of supervision and sanction on work discipline throught motivation as an intervening variable. The sample used was 66 employes at CV. Mubarokfood Cipta Delicia Kudus. Data collection uses a questionnaire method which is distributed directly to responden. Hypothesis testing was carried out using Partial Least Square 4.0 software. The research results show that supervision has a significant effect on motivation, but other results say that sanction have no effect on motivation. Supervision has a significant effect on work discipline, sanction have no effect on work disiplin, and motivasion has a significant effect on work discipline. This research also tests the indirect effect on work discipline which proves that motivation mediates supervision of work discipline. The result of this research are that the better the supervision, the better employee work discipline will be, but efforts to improve work discipline will increase if motivation can increase supervision so that employees will be more disciplined.